Sensores para detecção de hidratos por espectroscopia de impedância elétrica - Longo, Jean Paulo Nakatu (2020)
Impedance sensors, in which the measurand causes a variation of an electrical sensor property such as resistance or capacitance, are applied in this work to monitor fluids in industrial processes. In the field of oil and gas production, a current need is to monitor the formation and growth of hydrates. Hydrates are solid crystalline structures, which may form in the oil stream under certain pressure and temperature conditions. Such hydrates may disrupt the production causing risks and/or increasing productions costs. In the current industrial instrumentation scenario, there is no established detection technique for monitoring the formation of hydrates within the pipelines. In this work, electrical impedance spectroscopy is applied for this purpose, which is a robust, simple and low-cost technique. Hence, the electrical signature of each substance under analysis is evaluated. Besides the use of commercial sensing cell, a dedicated sensor was designed and constructed based on a concave plates geometry with the aim to be applied in pipes. Allied to impedance measurements in the range 40 Hz to 5 MHz, the formation and growth of solids was monitored. Initially static experiments were carried out with known substances for sensor calibration. Water freezing experiments were also performed, since ice has several similarities with hydrates. Finally, an experiment using a model substance (Tetrahydrofuran) was performed for hydrate formation. Thus, impedance spectroscopy is a promising technique to be applied in flow processes to help in monitoring hydrates